'I feel like Sophie Scholl': the (mis)appropriation of icons of anti-Nazi resistance in contemporary Germany. (20th October 2021) - Neumann, Klaus
ABSTRACT: Germany's Covid-19 protesters and members of the far right have tried to appropriate two key historical figures associated with the German anti-Nazi resistance, Sophie Scholl (1921–1943), who distributed anti-government leaflets, and Claus Schenk Graf von Stauffenberg (1907–1944), the mastermind of the failed coup of 20 July 1944. Neumann places these attempts in the context of the afterlives of Scholl, Stauffenberg and aspiring Hitler assassin Georg Elser (1903–1945). First, he argues that the far right's attempt to claim Stauffenberg should not be read as a move to deny the Holocaust, nor to reject Germany's responsibility for it, but rather to distance itself from Holocaust deniers and shift public discourses about German identity and history. Second, he argues that Covid-19 protesters have identified with Scholl because she has been considered the quintessential 'good German', she cannot be located on a left–right political spectrum and she represents German resistance as well as victimhood. Finally, he suggests that the success of these attempts to appropriate historical figures points to a lack of knowledge not about Nazi Germany's victims, or about Scholl and Stauffenberg themselves, but rather about the nature of the Nazi regime.